Modelling Of Park And Ride Programme For Penang Bridge Express Shuttle Transit (Best) - Alpi, Mustaqin (2017)
Currently, most big cities in Malaysia are confronted with traffic congestion, especially during the morning and evening peak hours. This may be attributed to the nation’s rapid growth in vehicle population. As the existing road capacity is unable to accommodate the vehicle capacity, the traffic situation is getting worse. Drivers have to face longer travel times on a daily basis, and this adversely affects productivity, and quality of life. The role of public transport is very essential in solving this problem. However, the public transport system must be in place and it has to be efficient to attract the public. In Malaysia, the Park and Ride concept is quite new. Currently, the Park and Ride system is mainly applied to rail based public transport. The Penang State Government is collaborating with Rapid Penang for a new bus service concept with the Park and Ride program especially for factory workers in the Free Trade Zone (FTZ) area in Bayan Lepas. The purpose of this program is to reduce the severity of traffic jams especially on the First Penang Bridge to reduce the number of private vehicles entering Penang and also to promote the usage of public transport in Penang. This service is fully subsidized by the Penang State Government and has been operating since March 2011. This study was conducted to see the performance of the existing Penang Bridge Express Shuttle Transit (BEST) program and also to develop the Park and Ride model.The results show that the BEST FTZ program has been successful, as a whole, reaching 60%-70% of Penang State’s target of 1,000 users per day. The study also shows that there are three main factors affecting the use of this BEST FTZ program, xvii namely; travel time and transportation cost, bus stop location and infrastructure supporting the public transport system. Finally, as a result of this study, models that can be used to estimate the future usage of BEST FTZ program were developed. However, based on existing performance, there is room for improving this service as well as getting direct input from users in real-time problems and challenges. At the same time, the Penang State Government is looking for the best formula to maintain and improve the level of use of this service.